Comparative Investigation of River Water Quality by OWQI, NSFWQI and Wilcox Indexes (Case study: the Talar River – IRAN) - Darvishi Gholamreza; Kootenaei Farshad Golbabaei; Ramezani Maedeh; Lotfi Eissa; Asgharnia Hosseinali (Archives of Environmental Protection, 2016)
Rivers are considered as one of the main resources of water supply for various applications such as agricultural, drinking and industrial purposes. Also, these resources are used as a place for discharge of sewages, industrial wastewater and agricultural drainage. Regarding the fact that each river has a certain capacity for acceptance of pollutants, nowadays qualitative and environmental investigations of these resources are proposed. In this study, qualitative investigation of the Talar river was done according to Oregon Water Quality Index (OWQI), National Sanitation Foundation Water Quality Index (NSFWQI) and Wilcox indicators during 2011–2012 years at upstream, midstream and downstream of the river in two periods of wet and dry seasons. According to the results of OWQI, all of the values at 3 stations and both periods are placed at very bad quality category and the water is not acceptable for drinking purposes. According to NSFWQI, the best condition was related to the upstream station at wet season period (58, medium quality) and the worst condition was related to the downstream in wet season period (46, very bad quality). Also the results of Wilcox showed that in both periods of wet season and dry season, the water quality is getting better from upstream station to the downstream station, and according to the index classification, the downstream water quality has shown good quality and it is suitable for agriculture.